Compliance to instructions on complete denture wear and care of patients in the UPCD prosthodontic section a descriptive study - Jacinto, Martin Francis K.
Introduction. In complete denture service, patient compliance to their dentist's instructions on the proper way of wearing and using the dentures, as well as their maintenance and care, plays a critical role in the treatment's success or failure. clinicians give either reinforced instruction (verbal instructions with a written list) or verbal instructions only. The difference in the method and the content of the post installation instructions may affect overall patient compliance to instruction.